Pengembangan Aplikasi Transformer Geogebra Berbasis Kemampuan Spasial Matematis - Sofia Ariyani; Himmatul Ulya; Ratri Rahayu (Center of Language and Cultural Studies, 2022)
This study aims to describe the development steps and to see the feasibility of the application of the GeoGebra Transformer as a learning medium based mathematical spatial abilities. This type of research is R&D using the ADDIE model which has been modified into ADD (Analysis, Design and Development). The development procedures are in the form of preliminary study analysis, needs analysis analysis, application design, validation of material experts and media experts, application limited test and application practicality test. The subjects in this study were students of class XI IPS 2 SMA NU Al-Ma'ruf Kudus. The data analysis used includes application development, application validity and application practicality. From the results of the study, it was found that the application developed was valid in terms of the assessment of material experts and media experts with an average score of 3,3. In the limited test the teacher and students gave a positive response to the application. The results of student responses to the GeoGebra Transformer application showed 78.9% of students gave a positive response. The teacher also gave a positive response to the GeoGebra Transformer application. Based on the results above, it can be concluded that the application of the GeoGebra Transformer is valid and practical, so that it can assist in the learning process regarding geometry transformation material.